Penerapan Psikologi Komunikasi dalam Mengatasi Gangguan Kesehatan Mental Pada Generasi Milenial - Rita Nurwulan Sari; Nunung Sanusi (Jurnal Media Komunika, 2023)
This study uses an interpretive qualitative approach with a phenomenological study type of research. Interpretive is a social system that interprets behavior in detail by means of direct observation. This interpretation comes from efforts to find explanations about social events based on the perspectives and experiences of research subjects. Communication psychology can be applied to survivors of mental health disorders, if there is effective communication in the communication process, the psychology of the communicator views communication as not only being able to speak but also requiring a convincing appearance. This means that the communicant does not only pay attention to what the communicator says and communication psychology also applies message psychology, the message referred to here is language, namely the conclusion of words. The power of language that can move and control something.